Selecting and Editing of Readers’ Letters in the Late 19th-Century Finnish Press - Sorvali Satu (United Kingdom, 2025)
This article shows that readers’ letters were selected and edited in late 19th-century Finnish newspapers for a variety of reasons. The criteria for selection and editing fit the four rules identified by professor of  journalism Karin Wahl-Jorgensen for the selection of readers’ letters in modern newspapers and it also demonstrates the 1890s newspapers’ role as gatekeepers and the continuing professionalization of  journalists. The editors considered the selection and editing of readers’ letters demanding and frustrating,  but they also saw themselves as men of principle, the defenders of the free word. The research sources  include the correspondence columns and the editors’ writing instructions to the readers in the 1890s press  of the Grand Duchy of Finland.